v.2 - Banerjee, B. N. (Allahabad, 1994)
This work brings together the key judgments of Justice V.R. Krishna Iyer, a former judge of the Supreme Court of India. Quoting Justice Iyer extensively, the volume provides a full account of his landmark judgments that are widely interpreted and admired.
Keywords: Civil appeals-Law